2021
DOI: 10.1063/5.0039228
|View full text |Cite
|
Sign up to set email alerts
|

Wall friction should be decoupled from fluid viscosity for the prediction of nanoscale flow

Abstract: The accurate determination of fluid viscosity based on the microscopic information of molecules is very crucial for the prediction of nanoscale flow. Despite the challenge of this problem, researchers have done a lot of meaningful work and developed several distinctive methods. However, one of the common approaches to calculate the fluid viscosity is using the Green–Kubo formula by considering all the fluid molecules in nanospace, inevitably causing the involvement of the frictional interaction between fluid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Configurations of water confined in graphene nanochannels are different from those in bulk due to the confinement effects by the channel walls (Sun et al, 2020;Zhou et al, 2021;Zhao et al, 2020a;Zhao et al, 2020b;Zhao et al, 2020c). Specifically speaking, the repulsive force confines the water molecules in the nanochannel, while the potential well or adsorption interaction changes the structure of confined water (Zhao et al, 2020b).…”
Section: Density Distribution and Hydrogen Bondmentioning
confidence: 99%
See 2 more Smart Citations
“…Configurations of water confined in graphene nanochannels are different from those in bulk due to the confinement effects by the channel walls (Sun et al, 2020;Zhou et al, 2021;Zhao et al, 2020a;Zhao et al, 2020b;Zhao et al, 2020c). Specifically speaking, the repulsive force confines the water molecules in the nanochannel, while the potential well or adsorption interaction changes the structure of confined water (Zhao et al, 2020b).…”
Section: Density Distribution and Hydrogen Bondmentioning
confidence: 99%
“…As an effective and powerful alternative tool, molecular dynamics (MD) simulation has presented excellent performance in the study of thermophysical properties of water at nanoscales, such as viscosity (Neek-Amal et al, 2016;Zhou et al, 2021), thermal conductivity (Zhao et al, 2020a;Zhao et al, 2020b), diffusion coefficient (Zhao et al, 2020c), and dielectric constant (Hamid et al, 2021). And it becomes a common sense that molecular behaviors of water under nanoconfinement deviate from bulk behaviors (Sofos et al, 2013;Sofos and Karakasidis, 2021) because of the large surface-to-volume ratio and the enhanced effects of surface properties including surface wettability and surface morphology (Shadloo-Jahromi et al, 2020;Shadloo-Jahromi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, defining the distance of the hydrodynamic interface from the wall as Δ hyd ≈ 6 Å, the system size appearing in eqs and is properly taken to be L hyd ≡ L – 2Δ hyd , corresponding to a volume of V hyd = AL hyd containing on average ⟨ N hyd ⟩ particles. It has recently been shown that such a decomposition is crucial to obtain the correct value of the bulk viscosity from the mobility and velocity profiles …”
mentioning
confidence: 99%
“…Previous studies have revealed that surface interactions have a significant effect on the behavior of nearest molecules of the surface and induce unique phenomena in nanospaces with dimensions of 10 0 nm, such as the change of water structure in silica nanopores. 7,8 Even in nanospaces with dimensions of 10 2 nm, which are 100 times larger than nanotubes and nanopores, we have revealed unique water properties such as 4 times higher viscosity, 9, 10 3 times lower dielectric constant 11 and 8 times higher proton diffusion coefficent 12 than those of bulk water. Based on nuclear magnetic resonance spectroscopy (NMR) data analysis, we revealed that the motion of water molecules is restricted nanochannels, and suggested a hypothesis of a loosely-structured water phase within 50 nm of the surface generated by interactions between silanol groups and water molecules.…”
Section: Introductionmentioning
confidence: 87%